Creating efficient bungalow interior and exterior designs using GIS story maps / Muhammad Aiman Khairil Nazri and Muhammad Aqmar Darwisy Muhammad - Khairil Nazri, Muhammad Aiman; Muhammad, Muhammad Aqmar Darwisy (Universiti Teknologi MARA (UiTM), 2024)
The ease of making changes inspired Revit's name, a contraction of Revise-Instantly. At the heart of Revit is a parametric change propagation engine that relies on a new technology, context-driven parametric, which is more scalable than the variation- and history-driven parametric used in mechanical CAD software. Revit required for Autodesk Revit is a powerful cloud-based tool for managing BIM workflows that can accelerate and improve the design process for anyone in the AEC industry.